Early life nutrition and the opportunity to influence long-term health: an Australasian perspective. (26th January 2016) - Davies, P. S. W.; Funder, J.; Palmer, D. J.; Sinn, J.; Vickers, M. H.; Wall, C. R.
Abstract : There are now significant data to support the hypothesis that early life nutrition in the fetus, infant and young child can have profound effects on long-term health. This review considers some of this evidence with specific reference to the current burden of disease in Australia and New Zealand. As the findings of further research become available, recommendations on optimizing early life nutrition should be formulated and made widely available as part of the preventative health policy agenda in both Australia and New Zealand.